Big data techniques and technologies in geoinformatics - Karimi, Hassan A. (CRC Press, Taylor & Francis Group, 2014)
Preface What is big data? Due to increased interest in this phenomenon, many recent papers and reports have focused on defining and discussing this subject. A review of these publications would point to a consensus about how big data is perceived and explained. It is widely agreed that big data has three specific characteristics: volume, in terms of large-scale data storage and processing; variety, or the availability of data in different types and formats; and velocity, which refers to the fast rate of new data acquisition. These characteristics are widely referred to as the three Vs of big data, and while projects involving datasets that only feature one of these Vs are considered to be big, most datasets from such fields as science, engineering, and social media feature all three Vs.